David and Goliath - Rich, Richard; Nest Entertainment, Inc.; Rich Animation Studios (Coppell, TX : Nest Entertainment, 2005)
David, a young shepherd boy who likes poetry and music, seems an unlikely candidate to save his nation from ruin. But when nine-foot Goliath defies Israel and blasphemes God, young David leaps into action in this story of courage, faith and daring, and earns his place as one of the greatest heroes in the Bible.
Includes Read-A-Long Sing-A-Long DVD.
Includes Reource & Activity Book.
"Premium website accessible through DVD-ROM"--Container.
"NEST complete learning system."
Produced by Richard Rich, Jared F. Brown ; screenplay, Brian Nissen ; music, Lex De Azevedo.
DVD ; 2-channel Dolby digital surround sound.
Keywords: David, -- King of Israel -- Juvenile films; Bible stories; Animated films; Children's films